A New Spiropyran Hydrazone as an Unusual Colorimetric Sensor for Detection of Cu2+ and Cr3+ Based on Aggregation‐Induced Enhancement Effects in Aqueous Solvent Mixtures. Issue 31 (18th August 2022) - Li, Zongchen; Xiong, Hui; Liang, Hua; Chen, Wenting; Tian, Qiang; Yan, Minhao; Su, Haifeng; Royal, Guy
Abstract: Though many improvements have been made on fluorescence probes for respective detection of Cu 2+ and Cr 3+, multiply detect of the ions by a simple colorimetric way in high water content solution sensors remains scarce. In this work, a novel spiropyran hydrazone, [(E)‐(2‐hydroxy‐1‐naphthyl)methylidene][(E)‐[1′, 3′, 3′‐trimethyl‐6‐(2‐methylprop −2‐yl)‐1′, 3′‐dihydrospiro[chromene‐2, 2′‐indole]‐8‐yl]methylidene]hydrazine (NA‐SP), which shows aggregation‐induced enhancement effects (AIEE) phenomena in EtOH (ethanol)/H2 O and THF (tetrahydrofuran)/H2 O media, has been developed. It can detect Cu 2+ colorimetrically having a sensitivity of 105 nM in EtOH/H2 O (40/60, v/v) with an unusual specific tandem‐response to Cr 3+ at a detection limit of 151 nM in addition with a wide pH range of 4–10. Mechanism investigations by HRMS, 1 H NMR and UV‐Vis spectroscopy have verified that the response to Cr 3+ is based on the cooperative effect between NA‐SP and Cu 2+, instead of the replacement of Cu 2+ by Cr 3+ . Moreover, NA‐SP shows a robust AIEE‐caused recognition for Cu 2+ in THF/H2 O (20/80, v/v) with a detection limit of 16.5 nM. Real water tests indicate that the probe has potential detection application for Cu 2+ in environmental situations. This contribution presents a new spiropyran sensor for the detection of Cu 2+ and Cr 3+ in aqueous solutions through an uncommonly colorimetric way. Abstract : A novel naphthalene‐spiropyran derivative, NA‐SP, has been developed for metal ion detection, which will transform its structure through ring‐close to ring‐open caused by certain external stimulation. The probe is weak fluorescent in pure ethanol (EtOH) and tetrahydrofuran (THF) solvent, whereas it shows aggregation‐induced enhancement effect (AIEE) in their aqueous media. It exhibits specific chromogenic response to Cu 2+ in EtOH/H2 O (40/60, v/v) with time controlled colorimetric recognition to Cr 3+ . Meanwhile, NA‐SP is proved to be a fluorescent sensor toward Cu 2+ in THF/H2 O (20/80, v/v) with a bit different aggregation mode from that in ethanol aqueous solution. This work provides a simple and colorimetric method to detect Cu 2+ and Cr 3+ distinctively in aqueous situations.